Antimicrobial effect of Waterborne polyurethane-based cellulose nanofibril/silver nanoparticles composites and Acacia concinna (Willd.) DC extract (shikakai) - Taung Mai, Lu Lu; San, H’ng Paik; Aung, Min Min; Uyama, Hiroshi; Mohamed, Ainun Zuriyati; Kamal Bahrin, Ezyana; Masarudin, Mas Jaffri; Mohamad Zulkifli, Azra Afrina; Chew, Tung Woey (Multidisciplinary Digital Publishing Institute, 2024)
Antimicrobial coatings are becoming increasingly popular in functional material modification and are essential in addressing microbial infection challenges. In this study, the phytochemical and antimicrobial potential of aqueous, 80% methanol and 80% ethanol pod extracts of Acacia concinna (Willd.) DC (AC) and its application in the green in situ (one pot) synthesis of silver nanoparticles on Cellulose nano fibrils (CNF) and Waterborne polyurethane (WPU) were prepared. The phytochemical evaluation of Acacia concinna crude extracts showed the presence of alkaloids, flavonoids, phenols, tannins, terpenoids, saponins, steroids. The surface plasmon Resonance peak of CNF/AC-AgNPs was 450 nm and the FTIR result confirmed functional groups such as carbonyl, phenols and carboxyl were present which was important for the bio-reduction of silver nanoparticles. The crude AC aqueous pods extract against Gram-positive and Gram-negative bacteria compared with AC ethanol and AC methanol extracts. The WPU/CNF/AC-AgNPs composite dispersion was also good in terms of its antibacterial activities. The WPU/CNF/AC-AgNPs nanocomposites could be applied as bifunctional nanofillers as an antimicrobial agent in food packaging systems and other biological applications.